Sipping Sustainability: Exploring the Green Marketing Mix Driving the Purchase of Oat M*lk Oatside - Aryani, Miranti Siti Nur Tri; Samaria, Sarah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
The issue of climate change due to global warming has occurred partly due to the significant increase in carbon emissions over the last few decades. This has created a market demand for products that have minimal adverse effects on the environment, also known as eco-friendly products. One of the popular eco-friendly products is oat milk. Despite the environmental issues highlighted and the product quality offered, the popularity of Oat M*lk Oatside remains low, and its higher price compared to cow's milk may influence purchasing decisions. This study aims to determine whether green product, green price, green place, and green promotion have an impact on the purchasing decisions of Oat M*lk Oatside. This study uses a quantitative approach, targeting the Instagram followers of @oatside, totaling 52,807, and a sample size of 100 people was obtained using purposive sampling, with criteria being Oat M*lk Oatside consumers residing in Jakarta. Data processing results show that Green Product and Green Promotion do not influence Purchasing Decisions, whereas Green Price and Green Place positively influence Purchasing Decisions. Green Price has a weak influence of 34.4%, and Green Place has a weak influence of 21.6% on Oat M*lk Oatside purchasing decisions.